Synergistic enhancements in the performances of dye‐sensitized solar cells by the scattering and plasmon resonance of Au‐nanoparticle multi‐shell hollow nanospheres. (1st April 2020) - Bai, Lihua; Liu, Jiaxian; Tang, Yiwen; Wang, Chun; Wen, Junqing; Wu, Hua; He, Wanlin; Sun, Ruijuan
Summary: Novel multi‐shell hollow SiO2 @Au@TiO2 (HSAT) nanospheres are synthesized by multi‐step method. Composite photoanodes and Dye‐sensitized solar cells (DSSCs) with different amount of HSAT nanospheres are studied. The study indicates that the HSAT nanospheres have enhanced the scattering and absorption of incident light in the photoanode, reduced the interface transmission resistance, increased the electron lifetime, and thus significantly improved performance of DSSCs. The maximal J sc and photoelectric conversion efficiency (PCE) obtained in the optimal DSSC doped with HSAT of 3.0% are 15.83 mA cm −2 and 7.21%, greatly enhanced by 21.0% and 20.4%, respectively, compared with those of the pure TiO2 ‐based DSSC. These remarkable enhancements in DSSCs performance can be attributed to the synergistic and complementary effects of the localized surface plasmon resonance and strong light scattering of HSAT nanospheres, which has significantly improved the absorption and utilization on incident light and thus the PCE of the DSSCs. Such synergistic and complementary effects of the different functions are also likely expected to play roles in the performance improvements in other solar cells. Abstract : Novel multi‐shell hollow SiO2 @Au@TiO2 (HSAT) nanospheres are prepared. Enhancements of 21.0% in J sc and 20.4% in photoelectric conversion efficiency (PCE) are obtained HSAT‐dye‐sensitized solar cells (DSSC). Enhancements are attributed to dual‐synergy of strong scattering and the LPSR of HSAT. Multi‐shell hollow HSAT architecture provides strong scattering to enhance PCE of DSSC.